Indigenous Agency and Normative Change from ‘Below’ in Russia: Izhma-Komi’s Perspective on Governance and Recognition - Peeters Goloviznina, Marina (Arctic Review on Law and Politics, 2019)
The article addresses the issue of indigenous agency and its influence on the contestation of indigenous rights norms in an extractive context from the perspective of organizations representing people, whose recognition as ‘indigenous’ is withheld by the Russian authorities. The article argues that a governance perspective and approach to recognition from ‘below’ provides a useful lens for comprehensively exploring strategies on norms contestation applied by these groups in the authoritarian normative context of Russia. Based on findings from a case study of Izhma-Komi organizations in the northwest Russian Arctic, the article identifies three strategies utilized by these organizations. By mobilizing inter-indigenous recognition, forging alliances with environmentalists and negotiating with an oil company, Izhma-Komi organizations have managed to extend certain rights and power previously not granted to them in an extractive context locally.